Modern Etiotropic Therapy of Influenza and ARVI in Adult Patients with Premorbid Pathology - V. K. Verevshchikov; E. K. Shemyakina; A. U. Sabitov; N. A. Batskalevich (Антибиотики и Химиотерапия)
An open comparative observational study of the clinical efficacy and safety of riamilovir (Triazavirin™) in patients over age 18 with influenza and acute respiratory viral infections (ARVIs) was conducted during the epidemic seasons of2016-2017 and 2017-2018. Clinical efficacy and safety of riamilovir (Triazavirin™) in groups of patients with influenza and ARVI was demonstrated. The use of riamilovir (Triazavirin™) allowed to achieve rapid positive dynamics in the management of febrile-intoxication and catarrhal-respiratory syndromes; it was equally effective in patients who did not immediately seek professional help.